Active commuting patterns at a large, midwestern college campus. - Bopp, Melissa; Kaczynski, Andrew; Wittman, Pamela (My University, 2011)
Objective: To understand patterns and influences on active commuting (AC) behavior. Participants: Students and faculty/ staff at a university campus. Methods: In April–May 2008, respondents answered an online survey about mode of travel to campus and influences on commuting decisions. Hierarchical regression analyses predicted variance in walking and biking using sets of demographic, psychological, and environmental variables. Results: Of 898 respondents, 55.7% were female, 457 were students (50.4%). Students reported more AC than faculty/staff. For students, the models explained 36.2% and 29.1% of the variance in walking and biking, respectively. Among faculty/staff, the models explained 45% and 25.8% of the variance in walking and biking. For all models, the psychological set explained the greatest amount of variance. Conclusions: With current economic and ecological concerns, AC should be considered a behavior to target for campus health promotion.
Keywords: Active commuting; Community health; Health education; Physical activity; Transportation